2010
DOI: 10.1088/1748-9326/5/2/024010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of fungal spores to particulate matter in a tropical rainforest

Abstract: The polyols arabitol and mannitol, recently proposed as source tracers for fungal spores, were used in this study to estimate fungal contributions to atmospheric aerosol. Airborne particulate matter (PM 2.5 and PM 10 ) was collected at Jianfengling Mountain, a tropical rainforest on Hainan Island situated off the south China coast, during spring and analyzed for arabitol and mannitol by high-performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD). The average concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
77
1
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 63 publications
(86 reference statements)
14
77
1
16
Order By: Relevance
“…The highest correlation (r = 0.86) is between arabitol and mannitol. Similarly high arabitol/mannitol correlations are reported in other studies (Bauer et al, 2008a;Zhang et al, 2010;Burshtein et al, 2011;Liang et al, 2013). Arabitol and mannitol are only moderately correlated with fungal spores (r = 0.51 and 0.49, respectively).…”
Section: Predictability Of Bioaerosol Indicators From Each Other and supporting
confidence: 84%
“…The highest correlation (r = 0.86) is between arabitol and mannitol. Similarly high arabitol/mannitol correlations are reported in other studies (Bauer et al, 2008a;Zhang et al, 2010;Burshtein et al, 2011;Liang et al, 2013). Arabitol and mannitol are only moderately correlated with fungal spores (r = 0.51 and 0.49, respectively).…”
Section: Predictability Of Bioaerosol Indicators From Each Other and supporting
confidence: 84%
“…The spores contain ARL and MAL as storage substances. Correlation between the fungal spore count and their concentration was verified in the PM 10 size fraction Zhang et al, 2010). Mannitol is one of the common energy and carbon storage molecules produced by various organisms, including bacteria, yeasts, fungi, algae, lichens and many plants, but its major suspension into the air is often expected to be linked primarily to fungal spores under ordinary atmospheric conditions.…”
Section: Introduction and Objectivesmentioning
confidence: 89%
“…In pristine tropical rainforest air, fungal spores account for up to Â45% of coarse particulate matter. Thus, the properties and effects of fungal spores may be particularly important in tropical regions where both, physico-chemical processes in the atmosphere and biological activity at the Earth's surface are particularly intense (Graham et al, 2003;Gilbert, 2005;Elbert et al, 2007;Po¨schl et al, 2010;Zhang et al, 2010), but chemical tracers typical of fungal spores have also been reported in aerosols from semi-arid and arid sites . Most airborne fungi belong to the divisions of Ascomycota and Basidiomycota (Fro¨hlich-Nowoisky et al, 2009).…”
Section: Fungal Spores and Fragmentsmentioning
confidence: 99%